Pursuing the universal: formalism, pragmatism and the project of modernity in contemporary critical democratic theory - Coleridge, B (2020)
This thesis critically evaluates the role of form and formalism in contemporary Frankfurt School critical democratic theory’s treatment of ethical pluralism. It examines how three contemporary theorists, Jurgen Habermas, Rainer Forst and Alessandro Ferrara, deploy methodological formalism, and a certain ideal of aesthetic or theoretical ‘form’, in support of the Kantian ‘project of modernity’. The thesis has two related aims: the first is to diagnose and critically evaluate the role of form and formalism as an instrument of mediation between ethical identity, value pluralism and the ‘project of modernity.’ In the course of identifying and assessing the intellectual resources that underpin the role of form and formalism in the relevant critical theories of democracy, this thesis argues that the strategies for normative and constitutional integration pursued by Habermas, Forst and Ferrara suffer from a hermeneutical deficit. Consequently, while they set out to develop an ethically non-impositional framework for negotiating between normative universality and ethical particularity, these three theorists also continue several of the weaknesses of Kantianism, including its dichotomous separation of normative ‘form’ from the texture of ethical life and its resident meanings. While Habermas, Forst and Ferrara all seek creatively to integrate the insights of philosophical pragmatism by developing immanently grounded ‘inter-subjective’ theories of normativity, their deployment of form as an ethically diminutive binding agent displays a limited reflexivity regarding the ideological specificity of aesthetic and methodological formalism.